Earmarked Health Taxes as a Tool for Expanding the Fiscal Space for Health Care - STEPANOVA, O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
The article explores the prospects of introducing earmarked health taxes as a mechanism for expanding of the fiscal space for health care financing. It was determined that in the conditions of martial law in Ukraine and the increase in the debt burden on the budget, there is a need to use new fiscal mechanisms that will increase budget revenue. One new fiscal mechanism could be the use of earmarked health taxes. An analysis of the global best practice of earmarked health taxes was carried out. Earmarked health taxes items typically are goods that have a negative public health impact, such as alcohol, tobacco, sugar-sweetened beverages, salt, fat content, fast food, etc. The peculiarities and foreign experience of applying sugar-sweetened beverages taxes, as well as their rates, tax base and instrument, are considered in detail. It was determined that earmarked health taxes were implemented not only in countries with a high level of economic development, but also in conflict-affected countries. Attention is focused on the need to apply the principles earmarking for reservation of tax revenues for health care financing in order to ensure transparency and establish a clear relationship between the amount of tax revenues from earmarked health taxes and budget expenditures for health care financing. The potential challenges of the implementation of earmarked health taxes for the fiscal sustainability are identified. Measures to improve the development, substantiation and forecasting of the principles of implementation of earmarked health taxes are proposed.